+0  
 
0
98
1
avatar

Let f be defined by

f(x) = 2 - x if x < 1

f(x) = 2x - x^2 if x >= 1

Calculate f(-3) + f(0) + f(3)

 Jun 14, 2022

Best Answer 

 #1
avatar+579 
+2

f(x) = 2 - x if x < 1

f(x) = 2x - x^2 if x >= 1

 

f(-3): 2+3 = 5

f(0): 2-0 = 2

f(3): 2(3)-(3)^2 = -3

 

5+2-3 = 4

 

-Vinculum

 

smiley

 Jun 14, 2022
 #1
avatar+579 
+2
Best Answer

f(x) = 2 - x if x < 1

f(x) = 2x - x^2 if x >= 1

 

f(-3): 2+3 = 5

f(0): 2-0 = 2

f(3): 2(3)-(3)^2 = -3

 

5+2-3 = 4

 

-Vinculum

 

smiley

Vinculum Jun 14, 2022

29 Online Users

avatar